The Relationship between Commitment-based HR Practices and Organizational Performance: The Role of Organizational Learning Capabilities as a Mediator - Po Li Chia; Khulida Kirana Yahya Kirana Yahya; Tan Fee Yean (Information Management and Business Review, 2016)
This study intends to investigate the relationship between commitment-based human resource practices (CBHRP) and organizational performance of the multi-national organizations in Malaysia with the present of organizational learning capability (OLC) as the mediator. The data were collected from 150 multi-national organizations, using a survey questionnaire. The returned response rate was 97 percent. A relevant statistical analytical such as regression analysis was used to test the hypotheses set forth in this study. The outcome of the analysis showed that the relationship between commitment-based HR practices and organizational performance was influence by organizational learning capability. The results imply that the multi-national organizations should enhance their CBHRP and OLC to strengthen their organizational performance.